FEATURES OF ISLAM AND CHRISTIANITY REPRESENTATIVES’ INTERCULTURAL UNIVERSALS - Telepova, Nadezhda; Telepov, Mikhail (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Issues of intercultural universals among different ethnic and cultural groups’ representatives are becoming very relevant in various branches of scientific and applied knowledge. Religion is one of the factors of intercultural distance, which many ethnic psychologists stress in their research. On the other hand the features of intercultural universals among representatives of different religious groups are studied very little. The goal of the study is to consider intercultural universals and their degree among representatives of two religions: Islam and Christianity. To achieve this goal, we chose the following methods: diagnostics of the Cultural-Value Differential of a personality (CVD, G. Soldatova, S.Ryzhova), diagnostics of basic beliefs (World Assumption Scale, WAS, Janoff-Bulman), diagnostics on cultural preferences in the context of the universal “Individualism-Collectivism” (IC, M.Telepov, N.Telepova). The results of the study revealed that Christians and Muslims have a lot in common in manifestations of intercultural universals, which means that representatives of these religions have a serious basis for dialogue and building relationships. Statistically significant differences were found in terms of benevolence of world and self-control (according to diagnostics on the WAS). Statistically significant differences were also found in terms of peacefulness and openness among Christians (according to diagnostics of the cultural-value differential of a personality).